Consciousness of young consumers on the quality of denim jeans - Bernales, Mariel P.; Dizon, Angelita M. (1998.)
Mass production of homogeneous products is very prevalent in today's global market. Supply of commodities continuously increase while the difference among merchandise decreases. In the garment industry, among such commodities are denim jeans, dubbed as the universal staple clothing of today's generation. Consumers of all ages have been studied to have a general preference for jeans wear for casual days. However, it is the younger group of shoppers (age 15-24) that are those observed to have the highest liking for jeans wear. With the magnitude of producers offering almost homogeneous products, quality as a purchasing factor for the specific group of consumers is studied. A total of 55 respondents participated in the survey, each given a self-administered questionnaire. Respondents were first year to fifth year students of the University of the Philippines, Diliman campus with ages ranging from 16-23 years old. The mean of the frequency of quality features observed by the respondents indicated a moderate consciousness for the quality of denim jeans. Quality consciousness points derived from the survey were correlated with gender, budget, quantity of jeans owned, and frequency of use of jeans wear. There was no significant difference between the awareness of quality of the males from that of the females. Likewise, there was no correlation found between the number of jeans owned and quality consciousness. The frequency of use of jeans wear could not be studied because of insufficient data. The frequency of use of jeans wear could not be studied because of insufficient data. The survey also indicated the existence of an inverse relationship between quality consciousness and budget, which means that the lower the budget, he higher the quality consciousness and vice versa.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Jeans (Clothing); Consumer preferences -- Philippines